CASCADING EXPLOITATIONS: THE CELEBRITY NUDE PHOTO HACK AS DIGITAL PHENOMENON - Lawson, Caitlin (AoIR Selected Papers of Internet Research, 2015)
This article employs a triadic critical framework to examine the implications of the celebrity nude photo hack at three levels: in the context of hacking more generally, at the level of their dissemination through social media, and as a form of online pornography. First, I explore the photo hack in the context of hacking more broadling, placing particular emphasis on its heavily gendered culture. Then, drawing primarily from van Dijck’s (2013) theory of social media logics, I explore the ways in which the hacked photos were disseminated through social media platforms like AnonIB, 4chan and Reddit. Finally, I present an analysis of the photos as online pornography and place them within the broader context of celebrity pornography. Pulling from Susanna Paasonen’s (2011) insights, I explore the digital materiality of the images and their complicated status as “amateur” pornography due to the fame of their subjects.